Application of ferimagnetic and ferromagnetic transformers in avionics and navigation systems - Ларін, Віталій Юрійович (Eastern-European Journal of Enterprise Technologies, 2012)
The article refers to the area of aircraft devices and navigation systems. It aims to analyze existing systems and devices of navigation and avionics, which contain in the structure ferrimagnetic and ferromagnetic primary and measurement transformers. It also aims to determine the ways of their improvement for the implementation in new and advanced navigation and avionics systems. The ferrimagnetic and ferromagnetic transformers are primary or measurement transducers, the sensors of which contain iron or its compounds and operate on the basis of magnetism or various magnetic effects: magneto-mechanical, magneto-striction, magnetoelastic, magneto-resistive, thermomagnetic, magnetooptical. The widespread application of these types of sensors was shown in the capacity of: meters of rotating velocity of motor shafts; pressure meters (frequency operation principle); devices to determine the course of the aircraft; devices to correct the inertial navigation systems. The application of modern integrated ferrimagnetic and ferromagnetic transformers for designing of high-quality devices of navigation avionics of UAVs was suggested